Depression and antidepressant treatment in the development of hypertensive disorders of pregnancy: Results from a prospective cohort study. (April 2023) - Galbally, Megan; Watson, Stuart J; Spigset, Olav
Background: Hypertensive disorders of pregnancy are associated with longer term cardiovascular risk. Understanding if depression or antidepressant use in pregnancy is associated with HDP is important in identifying those potentially vulnerable to poorer health in later life. This study examines if depression and antidepressants are associated with HDP. Methods: In all, 815 pregnant women were recruited within an Australian pregnancy cohort study at less than 20 weeks of pregnancy, all undertook the Structured Clinical Interview for the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, and were assigned to four groups for this paper: those with unmedicated depression meeting criteria for current depression ( n = 97), those taking selective serotonin reuptake inhibitors in early pregnancy ( n = 101), those taking serotonin and noradrenaline reuptake inhibitors in early pregnancy ( n = 31), and those without depression or taking antidepressant medication (control; n = 586). Women were then assessed again following birth. Hypertensive disorders of pregnancy were diagnosed according to the Society of Obstetric Medicine in Australia and New Zealand Guidelines. Results: Use of serotonin and noradrenaline reuptake inhibitors (SNRIs) (adjusted risk ratio = 9.10, 95% confidence interval = [3.82, 21.67]) and unmedicated depression (adjusted risk ratio = 3.11, 95% confidence interval = [1.32, 7.35]) were independently associated with significantly higher risk for developing hypertensive disorders of pregnancy compared to controls. Selective serotonin reuptake inhibitors (SSRIs) use did not confer any increased risk. Higher doses of SNRIs, but not selective serotonin reuptake inhibitors, were associated with significantly higher risk for developing HDP (adjusted risk ratio = 4.83, 95% confidence interval = [1.50, 15.58]). Conclusions: Our findings suggest that those with depression in pregnancy and/or on an serotonin and noradrenaline reuptake inhibitor should have closer surveillance for the development of hypertensive disorders of pregnancy. These findings support treatment of depression in pregnancy, however, also the consideration of class of antidepressant.